2013
DOI: 10.1016/j.theriogenology.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Protracted induction of parturition enhances placental maturation, but does not influence incidence of placental retention in cows

Abstract: As the etiopathology of retained placenta is still not resolved in cattle, we compared the effects of protracted induction of parturition (PIP) and conventional induction of parturition (SIP) on placental maturation and the occurrence of retained placenta. PIP was induced in 13 cows by administration of 1.3 mg dexamethasone im twice daily between Days 268 and 273 of gestation and 40 mg dexamethasone im on Day 274 of gestation. For SIP, 10 cows received a single injection of 40 mg dexamethasone on Day 274 of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
6
1
1
Order By: Relevance
“…It is well known that many factors are related to PR; however, the mechanisms underlying PR and the induction of parturition by corticosteroids are not well understood [46]. The differences between the current findings and the results of Hartmann et al might be due to the timing of induction and gestation lengths [13]. Some researchers have reported that gestation length was directly associated with the risk of developing PR [39,47,48].…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…It is well known that many factors are related to PR; however, the mechanisms underlying PR and the induction of parturition by corticosteroids are not well understood [46]. The differences between the current findings and the results of Hartmann et al might be due to the timing of induction and gestation lengths [13]. Some researchers have reported that gestation length was directly associated with the risk of developing PR [39,47,48].…”
Section: Discussioncontrasting
confidence: 64%
“…Although much effort has been focused on decreasing the rate of this complication [41][42][43], better results were obtained by previous studies, including treatment with long-acting corticosteroids [41,44,45]. Nevertheless, there are legal restrictions for the use of long-acting corticosteroids in food-producing animals in Europe [13,38] and induction using longacting corticosteroids has wide variability in response to treatment and lower predictability in terms of calving time [8,41]. Hartmann et al evaluated the use of low dosages of short-acting corticosteroids for the induction of parturition and showed that this alternative approach had a positive effect on the progress of placental maturation, but it did not have a positive effect on placental separation [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hartmann et al [20] reported that performing protracted induction of parturition by administration of dexamethasone twice daily between day 268th and 273rd of gestation results in increased placental maturation, but does not influence the incidence of placental retention in cows. Average incidence of fetal membranes retention for normal dairy cows range from 4%-18% [21].…”
Section: Discussionmentioning
confidence: 99%